Full‐scale shear tests on post‐tensioned bridge girders of existing bridges. (10th October 2017) - Huber, Patrick; Vill, Markus; Schweighofer, Anton; Kollegger, Johann
Abstract : Many post‐tensioned girders of existing bridges contain a low amount of transverse reinforcement. The shear strength of these girders, calculated according to current semi‐probabilistic design codes, like Eurocode 2, is often less than that required in the codes. In this paper, the experimental results of four shear tests on post‐tensioned bridge girders of existing bridges are presented. The specimens were extracted from two different road bridges, both built in 1959. In this paper, the results of this test series are used to analyze the shear behavior and failure modes of existing post‐tensioned bridge structures with a low amount of shear reinforcement. Furthermore, the experimental results are compared with the shear strengths calculated according to various design codes. Finally, the shear behavior is analyzed according to the zone‐based, shear assessment concept with its refined shear models. The calculation results agree well with the data from the experiments.